Intercom between rooms to room / Azlan Sulaiman and Fariz Fauzi - Sulaiman, Azlan; Fauzi, Fariz (2005)
Intercom is the one of the device will use in the smart home as similar like telephone system but it only use half duplex operation system. The user can place it at user house to house gate, door to screen visitor to user house,room to rooms, etc. It also the primary use of this type of system is in live or media productions where for example the vidoe director speaks to camera operators, or where the stage manager speaks to the stage hands and lighting operator, etc. The benefits of this system in the smart home as the security for user to identity the visitors, it also friendly user because it easy to cummunicate from Krona to rooms without moving to another room. From that explanation we can get many benefits from the intercom. Intercom also can make the communication very easy & effective.